Job Safety Analysis Dalam Identifikasi Potensi Bahaya Sebagai Upaya Pencegahan Kecelakaan Kerja Pada Pekerjaan Replating Dan Coating Kapal Di Pt. Dok Dan Perkapalan Surabaya (Persero) - Fachrul Juniarianto; Dwisetiono Dwisetiono (Departemen Teknik Kelautan Universitas Hasanuddin, 2022)
The use of modern machinery and installations and hazardous materials is increasing. In addition, a work environment that does not meet the requirements for occupational safety and health, hazardous work processes and nature, as well as an increase in the intensity of the operational work of the workforce, affects the increase in the number and seriousness of work accidents. The type of research used is descriptive quantitative research so that the data entered are in the form of words, sentences and pictures, which are then scored to determine the level of danger before carrying out the work. In conducting a job safety analysis, what is done is to determine the work to be analyzed, divide the work into several work steps or standard operating procedures, identify potential hazards, risk assessment, evaluate risk and determine the level of risk and prevention. The assessment of the risk value analysis on replating work has a value of up to 8, indicating the need for control measures in the process. Then the coating work on the fuel area and main deck also have a risk value of 8, so it is also necessary to take control measures on the coating process in that area.